Highly conjugated poly(N-heteroacene) nanofibers for reversible Na storage with ultra-high capacity and a long cycle life. Issue 38 (18th September 2018) - Gu, Tiantian; Zhou, Min; Huang, Bing; Liu, Mengyun; Xiong, Xiaolin; Wang, Kangli; Cheng, Shijie; Jiang, Kai
Abstract : cPAN-NFs, featured as a highly conjugated polymer with rich CN groups and 1D nanostructures, demonstrate a high Na-doping level with a reversible capacity of 527 mA h g −1, superior rate capability at 5 A g −1 and ultra-long lifespan over 3500 cycles. Abstract : Rechargeable Na-ion batteries based on redox-active polymers are highly desirable for the next generation of "green batteries". This study offers a simple and effective approach for the development of high performance organic anodes by introducing aromatic N atoms into conducting polymer backbones. Herein, for the first time, cyclized polyacrylonitrile (cPAN) is studied as a model of N-containing polyacene (PAc) and investigated as a novel organic anode. Benefiting from the highly conjugated backbones with rich CN groups, the cPAN nanofibers demonstrate superior Na storage performances including high reversible capacity (527 mA h g −1 at 50 mA g −1 ), outstanding rate capability (200 mA h g −1 at 5 A g −1 ) and an ultra-long lifespan (capacity retention of 99.4% over 3500 cycles). Ex situ structural characterization combined with theoretical calculations reveals that the introduction of aromatic N atoms with lone pair electrons could not only reduce the energy gaps of the PAc backbones, but also act as the redox-active centers. The results are promising and may pave the way towards the rational design of novel redox-active polymers for various energy storage applications.